Diversity of Grammars and Their Diverging Evolutionary and Processing Paths: Evidence From Functional MRI Study of Serbian - Progovac, Ljiljana; Rakhlin, Natalia; Angell, William; Liddane, Ryan; Tang, Lingfei; Ofen, Noa (Frontiers in Psychology, 2018)
We address the puzzle of “unity in diversity” in human languages by advocating the (minimal) common denominator for the diverse expressions of transitivity across human languages, consistent with the view that early in language evolution there was a modest beginning for syntax and that this beginning provided the foundation for the further elaboration of syntactic complexity. This study reports the results of a functional MRI experiment investigating differential patterns of brain activation during processing of sentences with minimal versus fuller syntactic structures. These structural layers have been postulated to represent different stages in the evolution of syntax, potentially engaging different brain networks. We focused on the Serbian “middles,” analyzed as lacking the transitivity (vP) layer, contrasted with matched transitives, containing the transitivity layer. Our main hypothesis was that transitives will produce more activation in the syntactic (Broca’s–Basal Ganglia) brain network, in comparison to more rudimentary middles. The participants (n = 14) were healthy adults (Mean age = 33.36; SD = 12.23), native speakers of Serbo-Croatian. The task consisted of reading a series of sentences (middles and transitives; n=64) presented in blocks of 8, while being engaged in a detection of repetition task. We found that the processing of transitives, compared to middles, was associated with an increase in activation in the basal ganglia bilaterally. Although we did not find an effect in Broca’s area, transitives, compared to middles, evoked greater activation in the precentral gyrus (BA 6), proposed to be part of the “Broca’s complex.” Our results add to the previous findings that Broca’s area is not the sole center for syntactic processing, but rather is part of a larger circuit that involves subcortical structures. We discuss our results in the context of the recent findings concerning the gene-brain-language pathway involving mutations in FOXP2 that likely contributed to the enhancement of the frontal-striatal brain network, facilitating human capacity for complex syntax.